The Hindu Kush seismic zone as a paradigm for the creation of ultrahigh-pressure diamond- and coesite-bearing continental rocks - Searle, M; Hacker, B; Bilham, R (2001)
Coesite eclogites and diamond-bearing ultrahigh-pressure (UHP) metamorphic rocks along ancient plate boundaries were mostly derived from quartz- and carbonate-bearing rocks originally formed close to the earth's surface. Their mineral assemblages and PT conditions require that they were subducted to depths of 90-130 km (27-40 kbar) and then brought back to the surface, still retaining evidence of their UHP formation. The geological record shows that continental-derived UHP rocks can be formed by subduction of thinned continental-margin crust beneath ophiolites (e.g., Oman ophiolite, west Himalayan ophiolites) or beneath island arcs (e.g., Kohistan Arc, Pakistan) as well as in continent-continent collision zones (e.g., Dabie Shan-Sulu Belt, Kazakhstan, western Norway, Alps). We present a model, based on the geometry of the seismically active Hindu Kush continental subduction zone and its restoration, assuming present-day plate motions, which explains how surficial graphite-rich shales and carbonates deposited along the northwest Indian plate margin were dragged down to these depths, anchored by the eclogitized leading edge of the thinned Indian plate crust. We suggest that coesite eclogite and diamond-bearing UHP metamorphism is occurring today at depth along the Hindu Kush seismic continental subduction zone.